A PROTO-MAEOTIAN HORSEMAN BURIAL FROM ADYGEA: RESULTS OF A COMPREHENSIVE STUDY - Leont'eva, Anna Stanislavovna; Erlih, Vladimir Roal'dovic; Eremenko, Kirill Ur'evic; Dobrovol'skaa, Maria Vsevolodovna; Abramova, Aleksandra Nikolaevna; Kiseleva, Dar'a Vladimirovna; Sarko, Fedor Sergeevic; Petrova, Dar'a Stanislavovna; Bulygina, Evgenia Stanislavovna; Nedoluzko, Artem Valer'evic; Spasskaa, Natal'a Nikolaevna (History, Archeology and Ethnography of the Caucasus, 2025)
This paper reports on a proto-Maeotian burial complex of a horseman warrior discovered in 2023 in the foothills of Adygea (N 44.22787800, E 40.12983900). The burial assemblage included weaponry, notably an axe-scepter, a Colchian fibula, an equine skeleton, and a set of bronze horse bridles contemporary with the Novocherkassk treasure. Based on these findings, the authors date the burial to the late 8th century BC. Comprehensive analyses, including natural science methods, were conducted on the burial. Anthropological examination determined the interred individual to be a male over 55 years of age who had sustained a cranial injury during his lifetime, potentially in military engagements. The authors propose that this elderly proto-Maeot horseman warrior may have participated in the “Cimmerian campaigns” in the Transcaucasia and Western Asia. Strontium isotope analysis of human and equine tooth enamel samples did not corroborate their habitation in the immediate vicinity of the burial site, nor did it indicate an origin in Western Transcaucasia. The unusual proportions of the horse skeletal remains prompted an investigation into a potential hybrid origin for the animal. However, detailed morphometric and molecular genetic analyses did not confirm the presence of a mule or hinny. Establishing definitive evidence for a specific local horse breed in the Early Iron Age of the North Caucasus necessitates dedicated genomic research.
Keywords: Adygea; proto-meotians; burial of a warrior-horseman; "Cimmerian campaigns"; bridle; scepter; Colchian fibula; strontium isotopes; molecular genetic analysis